Rumen fermentation and degradability in sheep fed crude glycerin from biodiesel production from frying oils - Menezes, Elizangela Soares; Araujo, Marcos Jacome de; Costa Torreao, Jacira Neves da; Torreao Marques, Carlo Aldrovandi; Bezerra, Leilson Rocha; Edvan, Ricardo Loiola; Silva, Silvokleio da Costa; Jesus Gomes, Tiago Gutemberg de [UNESP]; Carvalho Viana, Francisca Jakeline (Univ Estadual Londrina, 2023)
The objective of this study was to evaluate the dietary inclusion of crude glycerin (CG) derived from biodiesel production from residual frying oils, replacing corn, on intake, fermentation parameters, and rumen degradability of dry matter (DM) and crude protein (CP). Four rumen-cannulated sheep were fed diets containing 0, 25, 50, and 75 g CG kg(-1) of the total diet DM. A 4x4 Latin square design was adopted. To determine degradability, concentrate samples were incubated in the rumen at 0, 3, 6, 12, 18, 24, 48, and 72 h. Orthogonal contrasts were tested for linear and quadratic effects, which were considered significant when P < 0.05 and a trend when P < 0.10. The inclusion of CG did not influence the intakes of DM (average = 991.5 g day(-1)) or CP (average = 114.65 g day(-1)); however, ether extract (EE) intake increased linearly (P < 0.05), ranging from 20.8 to 36.7 g day(-1), respectively, for the CG levels of 0 and 75 g kg(-1) diet DM. There was no interaction effect (P > 0.05) between collection time and CG level on rumen pH or N-NH3. The lowest pH values were observed at 2 h (5.83) and 4 h (5.87) after feeding. Ammoniacal nitrogen (N-NH3) showed a quadratic decrease (P = 0.02), with a minimum value of 8 mg dL(-1) at the CG level of 41.5 g kg(-1) DM. The A fraction of the concentrate DM decreased quadratically (P = 0.05), with the lowest value (19.7%) occurring at the CG level of 74.1 g kg(-1) DM; the B fraction and effective degradability (ED; 8% h(-1)) decreased linearly (P < 0.05); and potential degradability (PD) tended to decrease (P < 0.10) with increasing CG levels. Crude glycerin did not affect the c fraction, lag time, or the ED (2% h(-1)) of concentrate DM. As regards CP, there was also no effect on fractions A (average = 41.5%), B (average = 51.0%), or PD (average = 92.4%); on the other hand, fraction c and ED increased linearly (P < 0.05), whereas lag time decreased linearly (P < 0.05) with increasing CG. In conclusion, the CG used in this study can be added up to the level of 75 g kg(-1) of the total DM of the sheep diet.
Keywords: Alternative feed; Ammoniacal nitrogen; Byproduct; Glycerol; Rumen disappearance